First detection and molecular identification of Anaplasma phagocytophilum in an introduced population of Reeve's muntjac (Muntiacus reevesi) in United Kingdom. (August 2020) - Duscher, Georg G.; Battisti, Elena; Hodžić, Adnan; Wäber, Kristin; Steinbach, Peter; Stubbe, Michael; Heddergott, Mike
Abstract: In the present study, we investigated blood samples of 196 invasive Reeve's muntjac ( Muntiacus reevesi ) and 91 native roe deer ( Capreolus capreolus ) originating from the same area in Thetford Forest in Eastern England for the occurrence of blood pathogens such as Anaplasmatacae, Rickettsiales and Piroplasmida ( Babesia spp., Theileria spp.) by using PCR. Babesia spp., Rickettsia spp. and Theileria spp. were not detected. Only two male (1%) Reeve's muntjacs and six (6.6%) roe deer were positive for Anaplasma phagocytophilum with 100% identity among their sequences. However, it is not clear whether Reeve's muntjac is less susceptible to infection, less susceptible to infestation by I. ricinus, or an infection in Reeve's muntjac is more lethal and therefore less positive animals are taken during hunting events. Highlights: 196 invasive Reeve's muntjac and 91 native roe deer were checked for blood pathogens. Reeve's muntjac and roe deer blood samples from the United Kingdom were positive for Anaplasma phagocytophilum with 100% identity. Reeve's muntjac may be less susceptible to infection, or less susceptible to positive ticks or an infection in Reeve's muntjac is more lethal